The Culture of Life’s Consumptive Behavior Against Potential Hypertension at Pangkep Community in South Sulawesi Indonesia - Darwis1 , Muzakkir 1, Masriadi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background. Every person has life needs that are met in different ways. There are those who meet theirneeds naturally and there are those who are excessive in fulfilling their needs. This causes people to behaveconsumptively. Consumptive behavior occurs in almost all walks of life. The habit of going to food courtsand fast food restaurants has led to consumptive behavior in modern society, they prefer something that isinstant, fast and delicious to consume and this has already happened in rural communities, especially inPangkep Regency. Patients with hypertension are the main causes of death (13.13%) and increasing cases(11,620) in Pangkep Regency in 2018 and 2019. Hypertension is a disease caused by various causes which areinterrelated to one another. One of the causes of hypertension is nutrition (fruit and vegetable consumptionhabits). Researchers want to analyze the relationship between consumer behavior in consumptive lifewith hypertension. Material and Methods. The study uses qualitative research with a phenomenologicalapproach. The sampling method uses snowball sampling. The study was conducted in 25 June 2018 - 31 Jan2019. The number of informants was 13 people. Data collection techniques namely interview techniques,observation, documentation. Data analysis techniques include the results of interviews, data reduction,analysis, data interpretation, and triangulation. Results. first, in looking at the consumptive behavior andculture of the Pangkep community, it is found that many hypertension sufferers begin with frequent visitsto the mall and consume fast food. Second, consumptive behavior and culture are risk factors for increasedhypertension sufferers. This is evidenced by the large number of patients visiting at the Health Service witha diagnosis of hypertension. Conclusion. The people of Pangkep Regency have a consumptive behavior sothat they are at high risk of developing obesity, hypertension.